Ana M. López : essays - López, Ana M.; Podalsky, Laura, 1964-; Tierney, Dolores (Albany, NY : State University of New York Press, 2023)
"Brings together Ana M. López's field-defining essays on Latin American film and media in one indispensable volume"--
Foreword / Ignacio M. Sánchez Prado -- Introduction: At the interface and beyond / Laura A. Podalsky and Dolores Tierney -- A cinema for the continent (1994) -- National history, transnational history (1998) -- Facing up to Hollywood (2000) -- Early cinema and modernity (2000) -- Film and radio intermedialities in early Latin American cinema (2017) -- From Hollywood and back : Dolores Del Rio, a (trans)national star (1998) -- The São Paulo connection : the Companhia Cinematografica Vera Cruz and O Cangaceiro(1998) -- Crossing nations and genres : traveling filmmakers (2000) -- Tears and desire : women and melodrama in the "old" Mexican cinema (1994) -- Our welcomed guests : telenovelas in Latin America (1995) -- Of rhythms and borders (1997) -- Mexico (2012) -- Before exploitation : three men of the cinema in Mexico (2009) -- (not) looking for origins : postmodernism, documentary, and America (1993) -- Revolution and dreams : the Cuban documentary today (1992) -- The battle of Chile : documentary, political process, and representation (1990) -- At the limits of documentary : hypertextual transformation and the new Latin American cinema (1990) -- A poetics of the trace (2014) -- Not only a question of color : Afro-Latino/a images in Latin American cinema today (1992) -- African roots : images of black people in Cuban cinema (1988) -- Sergio Giral on filmmaking in Cuba (1986-87) with Nicolas Peter Humy -- Are all Latins from Manhattan? : Hollywood, ethnography, and cultural colonialism (1991) -- Greater Cuba (1996) -- I (also) love Ricky : the oft-forgotten Cuban-in-the-text (2012) -- López on López : liminal words (2012) -- "Siete veces Ana" : an afterword / Nilo Couret.
Includes bibliographical references and index.
Description based on print version record.
In English.
eBooks on EBSCOhost
Keywords: Motion pictures -- Latin America -- History; Motion pictures -- Social aspects -- Latin America; Mass media -- Latin America -- History; Mass media -- Social aspects -- Latin America; Latin Americans in motion pictures; Performing arts; Video recordings; Electronic books; Cinéma -- Amérique latine -- Histoire; Cinéma -- Aspect social -- Amérique latine; Médias -- Amérique latine -- Histoire; Médias -- Aspect social -- Amérique latine; Latino-Américains au cinéma.; Arts du spectacle; Vidéos.; Livres numériques.; performing arts (discipline); video recordings (physical artifacts); e-books.; PERFORMING ARTS / Film & Video / History & Criticism; Latin Americans in motion pictures; Mass media; Mass media -- Social aspects; Motion pictures; Motion pictures -- Social aspects; Latin America; History